The laboratory evaluation of incorporating ceramsite into HMA as fine aggregates. (20th October 2018) - Che, Tiankai; Pan, Baofeng; Ouyang, Jian
Highlights: The pavement performance and thermal properties of CAM with different ceramsite ratio are studied. Effects of ceramsite replacement on pavement cooling of HMA are evaluated. Using ceramsite in HMA is an effective way to reduce pavement temperature and enhance dynamic stability. The optimal ceramsite ratio in HMA is given through considering pavement performance and cooling effect. Abstract: The aim of this paper is to explore hot asphalt mixture (HMA) with potential cooling capacity through adding ceramsite. Ceramsite asphalt mixtures (CAM) are prepared by adding ceramsite to replace fine aggregate with different ratio. Marshall and pavement performance tests were performed to test the pavement performance of CAM. Indoor radiation and outdoor radiation tests are carried out to evaluate the thermal properties of CAM. Results indicate that the Marshall Stability and dynamic stability of CAM increase with the increasing ceramsite ratio from 0% to 60%. The retained MS and low temperature performance of CAM nearly do not change with ceramsite ratio, but the tensile strength ratio decreases with ceramsite ratio. However, all values of the tensile strength ratio are above the requirements of specification. In the aspect of the thermal properties of CAM, the addition of ceramsite can effectively reduce the thermal conductivity of asphalt mixtures. Also, ceramsite is helpful in reducing the temperature of pavement and enhancing the ability of heat resistance, and the optimal effect can reduce the bottom surface temperature about 2.6 °C when ceramsite ratio is 60%. Because of the improvement in the dynamic stability and the thermal conductivity, CAM can have a good rutting resistance and the recommended ceramsite ratio is 60%.